Kualitas Daging Se’i Babi melalui Aplikasi Tepung Rosela - Matutina, Veronika; Sipahelut, Geertruida Margareth; Sabtu, Bastari (JURNAL KAJIAN VETERINER, 2024)
Se'i meat is a typical meat from East Nusa Tenggara which is made by smoking it. The meat is sliced ​​in small lengths, then smoked until cooked and has a distinctive taste. This study aims to determine the effect of rosella flour (Hibiscus sabdariffa L.) to organoleptic (colour, aroma, taste and tenderness); pH; TPC and E. coli pork. The research method uses a Complete Randomized Design (RAL) consisting of 4 treatments and 4 repetitions. The treatment consisted of P0: pork se’i meat without the addition of rosella flour, P1: pork se’i meat with the addition of rosella flour 0.5%, P2: pork se’i meat with the addition of rosella flour 1%, P3: pork se’i meat with the addition of rosella flour 1.5%. The organoleptic test of colour, aroma, taste and tenderness of pork meat was analysed using the Kruskal Wallis test followed by the Mann Whitney test, while the pH, TPC and E. Coli. analysed using ANOVA followed by Duncan's test to see any differences between treatments. The results showed that the application of roselle flour to pork se'i meat with different concentrations (0.5%, 1% and 1.5%) affected the organoleptic quality (colour, taste and tenderness) but did not affect the aroma of pork se'i meat. The addition of roselle flour can also lower the pH, TPC and E. coli pork. It is concluded that the higher the amount of rosella flour shows good results for the quality of pig meat because it increases the taste and tenderness and lowers the pH, TPC and E.coli of pork se’i.